(untitled) (Journal of the College of Education for Women, 2019)
The Arab Islamic Manuscripts in the science libraries humanly global heritage in different types of knowledge and science, as they were not confined to a particular flag but extended to include all kinds of science, and to facilitate the knowledge of these types of manuscripts has been necessary to operate them indexed in most libraries , because it is important in determining the size of those manuscripts and set them up and facilitate the work of the investigators, as well as the significance of indexing to know printed manuscripts in order to avoid repetition of the publication of the manuscript more than once, especially if the deployment is to be characterized by accurate scientific integrity and following the origins of the scientific method in achieving the manuscript, so the publishing heritage beginning Arab Islamic manuscript is the work on the indexing of its importance in providing the investigator with information needed for the manuscript, so colorful catalogs in all the world’s libraries, which included within them the most prominent Arabic manuscripts as well as anecdotes manuscripts and Nvaisha, and this is our research has provided a fraction of centers that have kept us this Arab and Islamic heritage, this does not mean the absence of others, especially in the personal libraries are undoubtedly spread throughout the Arab-Muslim world and looks forward to working with the indexing